Data Rating untuk Digital Signage di Universitas Kristen Petra menggunakan Kinect - Ivan Wijaya; Liliana -; Rolly Intan (Jurnal Infra, 2014)
Along with the growth of Technology, the usage of digital signage for a communication device is common in this digital world. And now Petra Christian University starting using digital signage that named DIVo. But for measuring this device are effective or not we need someone to count every person who pass by this device, and we need to count how many person who many readers who read DIVo as well. But for getting the data manually there will be many error. For example there will be human error that can make a mistake for counting how many person that passing by DIVo twice or even more, and we need many human resource to do this work because there are more than one DIVo in Petra Christian University.So we need some device that can detect people who passing by DIVo, and can detect thre reader face, and all of that thing can be done by using Kinect. Kinect is a device that made by Microsoft for gaming console named Xbox, this device is a input unit for Xbox so player doesn’t need a controlling device at all just using their body for playing. And using skeletal tracking and Face tracking inside Kinect SDK, this application can count how many person that passing by DIVo, and count how many person that read the DIvo and count how long the reader read DIVo. And using this device we can overcome this problem if we counting traffic using manual method.